P31 | MORPHOLOGICAL AND ULTRASTRUCTURAL MARKERS OF RADIATION-INDUCED ADIPOSE TISSUE DAMAGE (European Journal of Histochemistry)
Radiotherapy (RT) is utilized in approximately 50% of all cancer cases as curative treatment. High-energy Ionizing radiation causes direct DNA damage as well as indirect damage to cellular structures through the formation of reactive oxygen species, resulting in impaired metabolism, and ultimately cell death. Anticancer efficacy of RT relies on enhanced radiosensitivity of cancer cells, due to their extremely high proliferation rate. However, RT is associated with both acute and late toxicities. Among the latter, an increased risk of developing metabolic syndrome (MS) has been observed in childhood cancer survivors, possibly caused by long term effects on white adipose tissue (WAT)1. WAT morphology is tightly related to the function of the adipose organ, particularly in relation to MS2. Hence, we applied morphological and ultrastructural analyses to a murine preclinical model of RT exposure to detect early markers of RT-induced WAT dysfunctions. Corresponding molecular profiling was also obtained by means of bulk RNA sequencing. Ten-week-old C57BL/6J male mice were irradiated to the left hind limb with a total dose of 35 Gy. Animals in the control group did not receive any treatment. After 4 months animals were sacrificed and tissues removed and processed for transmission electron microscopy or RNA-seq analyses. In treated animals as compared to untreated controls both dermal and subcutaneous white adipocytes showed morphological alterations and signs of delipidation, including presence of intra-cytoplasmic clear vacuoles and electrontransparent areas. Characteristic signs of adipocyte death were also observed as peri-adipocyte “crown-like“structures3. Consistent with this, transcriptomics data showed marked dysregulation of key pathways involved in lipid metabolism. Our observations indicate that RT induces durable and extensive morpho-functional damage to the adipose organ, with a possible involvement in MS onset.